From enclave to linkage economies? A review of the literature on linkages between extractive multinational corporations and local industry in Africa - Michael W. Hansen (Danish Institute for International Studies (DIIS), 2014)
If African developing countries are to benefit fully from the current boom in foreign direct investment (FDI) in extractives (i.e. mining and oil/gas), it is essential that the foreign investors foster linkages to the local economy. Traditionally, extractive FDI in Africa has been seen as the enclave economy par excellence, moving in with fully integrated value chains, extracting resources and exporting them as commodities having virtually no linkages to the local economy. However, new opportunities for promoting linkages are offered by changing business strategies of local African enterprises as well as foreign multinational corporations (MNCs). MNCs in extractives are increasingly seeking local linkages as part of their efficiency, risk, and asset-seeking strategies, and linkage programmes are becoming integral elements in many MNCs' corporate social responsibility (CSR) activities. At the same time, local African enterprises are eager to, and increasingly capable of, linking up to the foreign investors in order to expand their activities and acquire technology, skills and market access. The changing strategies of MNCs and the improving capabilities of African enterprises offer new opportunities for governments and donors to mobilize extractive FDI for development goals. This paper seeks to take stock of what we know about the state of and driving forces of linkage formation in South Sahel Africa extractives based on a review of the extant literature. The paper argues that while MNCs and local enterprises by themselves will indeed produce linkages, the scope, depth and development impacts of linkages eventually depend on government intervention. Resource-rich African countries' governments are aware of this and linkage promotion is increasingly becoming a key element in their industrialization strategies. A main point of the paper is that the choice between different linkage policies and approaches should be informed by a firm understanding of the workings of the private sector as well as the political and institutional capacity of host governments to adopt and implement linkage policies and approaches.
Keywords: 300